Long-run dynamics between cost of quality and quality performance - Sturm, Sebastian; Kaiser, Gernot; Hartmann, Evi (International Journal of Quality and Reliability Management, 2019)
Purpose: The dynamics of quality performance and quality cost are gaining renewed interest in quality management literature. Using large sample secondary data, the purpose of this paper is to build up empirical evidence for increasing quality performance in manufacturing in the long-run. The authors then examine whether it is possible to reduce internal and external failure cost over time without increasing prevention and appraisal expenditures in return. Finally, a scale effect in reducing quality cost is measured to clarify the long-run dynamics between quality cost and quality performance. Design/methodology/approach: The authors conduct statistical analysis on a large sample secondary data set to reveal relationships between total cost of quality, its components and overall quality performance. Findings: Significantly higher quality performance and lower quality cost are observed in the long-run. Quality costs grow less than half as fast as sales volume, pointing to a significant scale effect in quality cost reduction. Practical implications: Businesses can use these implications for targeting failure costs and budgeting appraisal and prevention costs. Based on company-specific historical learning behavior through prevention and appraisal activities, an increasingly reliable prognosis of failure cost shall be possible. Originality/value: For the first time, quality performance and cost dynamics are assessed using a secondary data set with more than 400 observations. A scale effect for quality cost reduction is measured. The results are of great importance to quality management practice and research.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Manufacturing strategy; Operations management; Production economics; Quality costing; Quality management